Investigating Dutch Disease: The Case of Nigeria - Oyesanmi, Taiwo Alphonso (Eastern Mediterranean University (EMU), 2011)
ABSTRACT: This research study empirically investigates the presence of Dutch disease hypothesis in Nigeria when there is long run equilibrium, focusing on this concept of long run equilibrium between crude oil export and agricultural output covering the period 1970-2009 by using Johansen cointegration test, Vector Error Correction Model type of VAR, Impulse Response Function and Variance Decomposition while investigating this possible long run relationship then the study concentrated on two objectives. First main objective is to detect if there exist a negative relationship between crude oil export and agricultural output when crude oil export and the variables are normalized on agricultural output and the second aspect is to observe how innovations or shocks to the crude oil export explains the variations or changes in Agricultural output. In this study seven variables were used namely LAGR, LGDP, LXQcrudeoil, LREER, SRRATE, LRRATE, INFL to explain the Dutch Disease Hypothesis while transformation of variable to log help sort out the scaling problems with variables expressed in the above stated forms. The results are: (1) Cointegration among the variables using (Trace and maximum Eigen values) Johansen tests found cointegration of order (1) which means the variables move together in the long run and when normalized on LAGR, LXQcrudeoil has the expected sign and significant in explaining the expected relationship. (2) After finding cointegration, we proceed to Vector Error Correction (VEC), when LAGR is normalized on other variables, LXQcrudeoil has the same expected negative sign and it is significant in explaining the relationship. (3) Using Impulse Response Function, innovation in LXQcrudeoil is significant in explaining the negative changes in LAGR as expected. (4) Using Variance Decomposition, LXQcrudeoil explains about 20% variations in LAGR when shocks were applied. The findings show that, Dutch Disease hypothesis exist in Nigeria and cannot be ignored in Nigeria using these economic variables. Keywords: Dutch disease, impulse response function, variance decomposition, cointegration, Nigeria, maximum eigen value, hypothesis. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu araştırmada Nijerya‟da “Hollanda hastalığının” (Dutch Disease) mevcudiyetinin uzun dönem denge koşulları altında incelenmesi ampirik olarak yapılmaktadır. Ülkenin 1970-2009 dönemleri verileri kullanılarak ham petrol ihracatı ve tarımsal üretim arasındaki bir uzun dönem dengesinin varlığı ve bununla bağlantılı sınamalar Johansen Eştümleşme testi, Yöney Hata Düzeltme Modeli (VECM) ,Etki tepki İşlevi ve Değişirlik Ayrıştırması metodları kullanılarak araştırılmıştır. Çalışmada uzun dönem ilişkisi araştırılırken iki amaç gözetilmiştir. Birincisi ve çalışmanın ana teması değişkenlerin tarımsal üretime göre normalleştirildiğinde ham petrol ihracatı ile tarımsal üretim arasında ters yönde bir bağlantının sınanmasıdır. İkinci amaç ise ham petrol şoklarının veya yenileşimlerinin tarımsal üretimdeki değişmeleri nasıl etkilediğini araştırmaktır.Bu çalışmada LAGR, LGDP, LXCrudeOil, LREER, SRRATE, LRRATE,INFL başlıklı yedi adet değişken kullanılmıştır. Sırasıyla tarımsal üretim,Gayri safi yurt içi hasıla, ham petrol ihracatı, reel effektif döviz kuru, kısa ve uzun vadeli faiz oranları olarak belirlenen değişkenlerin ilk dördü veri ölçeklemesini sağlamak için logaritmik olarak ifade edilmişlerdir. 1) İz ve Özdeğer sınamaları sonucunda değişkenler arasında bir adet eştümleşme vektörü tesbit edilmiş olup, dolaysıyla bu değişkenlerin uzun dönemde birlikte hareket ettikleri gözlemlenmektedir. LAGR değişkenine göre normalleştirme yapıldığında ham petrol ihracatı (LXQcrudeoil) ile aralarında oluşan ilişkinin yönü beklendiği gibi çıkmıştır.2) Eştümleşme sınamasını müteakip Yöney Hata Düzeltme Modeli (VECM) tahmini yapılmıştır. Bu aşamada da LXQcrudeoil değişkeninin katsayısının beklenen negatif işarete sahip olduğu ve istatistiksel olarak anlamlı olduğu görülmüştür. 3) Etki tepki işlevi yöntemine göre LXQcrudeoil değişkeninde oluşan yenileşimin, beklenildiği gibi LAGR değişkeninde oluşan negatif değişimleri açıklamada anlamlı bulunduğu gözlemlenmiştir. 4) Değişirlik ayrıştırması uygulamasında LXQcrudeoil LAGR değişkenindeki değişimin yaklaşık %20‟sini açıklayabildiği tesbit edilmiştir. Bütün bu bulgular Nijerya‟da bir “Hollanda hastalığı” etkeninin varlığına işaret etmekte ve bu ekonomik değişkenler kullanıldığında sorununun gözardı edilemeyeceğini göstermektedir. Anahtar Kelimeler:Hollanda Hastalığı, Etki Tepki İşlevi, Değişirlik Ayrıştırması, Eştümleşme Testi, Nijerya, Maksimum Özdeğer, Hipotez.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2011. Supervisor: Assoc. Prof. Dr.Cem Payaslıoğlu.
Keywords: Economics; Nigeria - Economic Conditions; Dutch Disease--Impulse Response Function - Variance Decomposition; Cointegration - Nigeria - Maximum Eigen Value - Hypothesis